The Ustaša in Australia: A Review of Right-Wing Ustaša Terrorism from 1963-1973, and Factors that Enabled their Endurance - Kristy Campion (Salus Journal, 2018)
From 1963–1973, the Ustaša, a Croatian terrorist organisation, would find an unlikely safe haven in Australia. There, they established new Ustaša networks which trained new members, financed chapters overseas, launched incursions into Yugoslavia, and waged a terrorism campaign against the Yugoslav migrant community in Australia. In ten years, the Ustaša was found to be directly responsible for fifteen attacks, and inspired dozens more. It was not until 1973 that the Ustaša campaign in Australia came to an end, with a change in government, provoking a review of Australia’s law enforcement agencies. The Ustaša operated in Australia due to five major factors. Firstly, there was political sympathy for Croatian independence, which led to a reluctance amongst some officials to admit the Ustaša existed. Secondly, there was the political alignment of the Ustaša, which was favourably right wing at a time when Australia’s main enemy, communism, was on the left side of politics. Competing security jurisdictions and obscurity also undermined collaboration and counterterrorism efforts. Another factor was community relations, undermined by the language barrier and Yugoslav fear of retribution. Finally, strategic Ustaša targeting decisions enabled it to avoid provoking public censure.